Dysfunctional Family in Tabitha Suzuma’s Forbidden - Rani Anggi Adikasih; Anik Cahyaning Rahayu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines the portrayal of dysfunctional family in Tabitha Suzuma's Forbidden. It aims to identify the signs of dysfunctional family, analyze the causes of family dysfunction, and examine its psychological impacts on the main characters, Lochan and Maya. This study employs a qualitative descriptive research design using a psychological approach to literature. The data source is the novel Forbidden (2010) by Tabitha Suzuma, and the analysis is conducted using Murray Bowen's Family Systems Theory and Psychoanalytic Literary Criticism. The findings reveal that the Whitely family exhibits several signs of dysfunctional family, including low differentiation of self, triangulation, emotional cutoff, parentification (role reversal), and misplaced emotional attachment. The study also finds that parental neglect and absence, emotional instability, poor communication, and lack of emotional support contribute to family dysfunction. These conditions result in anxiety, emotional distress, low self-esteem, unhealthy emotional dependency, and social isolation experienced by Lochan and Maya. The findings suggest that dysfunctional family environments profoundly shape emotional development, psychological well-being, and interpersonal relationships, leading to emotional dependency and blurred family boundaries.